Morphological characterization and secondary metabolites profile of black pepper (Piper nigrum L.) genotypes from Sikkim - Gurung, K.; Manivannan, S. (Journal of Spices and Aromatic Crops, 2020)
Quantification of volatile oil and analysis of four major metabolites using HPLC was done in 24 black pepper genotypes collected from south Sikkim. The amount of volatile oil ranged from 2.01% to 0.022%. Secondary metabolites like piperine ranged from 2.75-0.022%, myrcene from 2.094-0.022%, alpha- phellandrene from 1.373-0.008% and linalool from 0.834-0.012%. Genotype 23 had the highest amount of myrcene and linalool, genotype 13 had the highest quantity of piperine and genotype 8 had high amount of alpha-phellandrene. The principal component analysis (PCA) of analyzed metabolites grouped the genotypes into four categories. The study revealed that some of the genotypes were as good as pepper varieties grown in traditional areas. These genotypes will be useful in crop improvement strategies and suitable for Sikkim Himalaya.